2016
DOI: 10.18026/cbusos.48113
|View full text |Cite
|
Sign up to set email alerts
|

Dolar Kuru’nun Borsa İstanbul-30 Endeksi̇ Üzeri̇ndeki̇ Etki̇si̇ Ve Aralarindaki̇ Nedenselli̇k İli̇şki̇si̇ni̇n İncelenmesi̇

Abstract: ÖZ Bu çalışmada Dolar Kuru ile Borsa İstanbul Ulusal 30 Endeksi (BİST-30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…First, the relationship between the two variables, regardless of whether it is short or long term, has been determined. Among these studies; Dornbush and Fischer (1980), Aggarwal (1981), Frankel, (1983, Hatemi andIrandoust (2002), Ayvaz (2006), Büberkökü (2008), Rahman and Uddin (2008), Ghazali et al ( 2008), Pekkaya and Bayramoğlu (2008), Kutty (2010), Savaş and Can (2011), Berke (2012), Benli (2015), Ceylan and Şahin (2015), Belen and Karamelikli (2016), Kendirli andÇankaya ( 2016 Eyüboğlu andEyüboğlu (2018) ), Delgado et al (2018), Tachibana (2018) Kumar (2019), Kayral (2020), as well as Uğur andBingöl (2020). Asad, et al (2022) also compared energy sources and found a relationship between stock values and exchange rates.…”
Section: Literature Surveymentioning
confidence: 99%
“…First, the relationship between the two variables, regardless of whether it is short or long term, has been determined. Among these studies; Dornbush and Fischer (1980), Aggarwal (1981), Frankel, (1983, Hatemi andIrandoust (2002), Ayvaz (2006), Büberkökü (2008), Rahman and Uddin (2008), Ghazali et al ( 2008), Pekkaya and Bayramoğlu (2008), Kutty (2010), Savaş and Can (2011), Berke (2012), Benli (2015), Ceylan and Şahin (2015), Belen and Karamelikli (2016), Kendirli andÇankaya ( 2016 Eyüboğlu andEyüboğlu (2018) ), Delgado et al (2018), Tachibana (2018) Kumar (2019), Kayral (2020), as well as Uğur andBingöl (2020). Asad, et al (2022) also compared energy sources and found a relationship between stock values and exchange rates.…”
Section: Literature Surveymentioning
confidence: 99%
“…The relationship between stock prices and exchange rates has been extensively studied by many researches. Some find positive association between the two [4,5] others discover negative relations [6,7] and even no relationship at all [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results suggest that there is positive bi-directional causal relationship from technology indices to exchange rate, but in terms of national 100, services, financials and industrials indices to exchange rate the paper does provide negative causality [15]. On the other hand, Kendirli and Çankaya (2016) analyze the causal relationship between the USD and Istanbul Stock Exchange National 30 Index from 2009:01 to 2014:12 monthly data and find no causal relationship between USD and BIST-30 index returns [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Döviz kuru ve hisse senedi ilişkisi konusunda; Qiao (1997), Bhattacharya & Mukharjee (2002), Fang & Miller (2002), Hatemi & Irandoust (2002), Nath & Samanta (2003), Misra (2004, Phylaktis & Ravazollo (2005), Tabak (2006), Ayaz (2006, Aydemir & Demirhan (2009), Kutty (2010), Kapusuzoğlu & İbicioğlu (2010), Zia & Rahman (2011), Savaş & Can (2011, Berke (2012), Ray (2012), Paramati & Gupta (2013), Büberkökü (2013), Şentürk & Dücan (2014), Ceylan & Şahin (2015), Kendirli & Çankaya (2015), Öncü, Çömlekçi, Yazgan & Bar (2015), Coşkun & Ümit (2016), Belen & Karamelikli (2016) gibi araştırmacılar, hisse senedi ve faiz oranları arasındaki ilişki konusunda ise Pearce & Roley (1985), Hardouvelis (1987), Flannery & James (1984), Cook & Hahn (1988), Bae (1990), Fung, Lie & Moreno (1990, Gjerde & Saettem (1999), Aras & Müslümov (2003), Davig & Gerlach (2006), Alam & Uddin (2009), Vejzagic & Zarafat (2013), Rana (2013), Sayılgan & Süslü (2011), Husain vd. (2014, Toraman & Başarır (2014) Bir zaman serisinde birden fazla kırılma olabileceğinden çoklu kırılmalı testler; tek kırılmalı veya kırılmasız testlerden daha güvenilir sonuçlar vermektedir.…”
Section: Alan Taramasiunclassified
“…Artan faiz oranları firma maliyetlerini etkileyecek maliyetler ise karlılığı etkileyecektir. Bu bağlamda artan faiz oranları karlılığı azaltacağından hisse senedi getirilerini azaltacak, diğer yandan yeni hisse senetlerinin alımını azaltacak ve hisse senedi fiyatının düşmesine neden olacaktır (Pearce & Roley, 1985;Bae, 1990;Husain, Zaman & Baloch, 2014;Toraman & Başarır, 2014 Döviz kuru ve hisse senedi ilişkisi konusunda; Qiao (1997), Bhattacharya & Mukharjee (2002), Fang & Miller (2002), Hatemi & Irandoust (2002), Nath & Samanta (2003), Misra (2004), Phylaktis & Ravazollo (2005), Tabak (2006), Ayaz (2006), Aydemir & Demirhan (2009), Kutty (2010), Kapusuzoğlu & İbicioğlu (2010), Zia & Rahman (2011), Savaş & Can (2011, Berke (2012), Ray (2012), Paramati & Gupta (2013), Büberkökü (2013), Şentürk & Dücan (2014), Ceylan & Şahin (2015), Kendirli & Çankaya (2015), Öncü, Çömlekçi, Yazgan & Bar (2015), Coşkun & Ümit (2016), Belen & Karamelikli (2016) gibi araştırmacılar, hisse senedi ve faiz oranları arasındaki ilişki konusunda ise Pearce & Roley (1985), Hardouvelis (1987), Flannery & James (1984), Cook & Hahn (1988), Bae (1990), Fung, Lie & Moreno (1990, Gjerde & Saettem (1999), Aras & Müslümov (2003), Davig & Gerlach (2006), Alam & Uddin (2009…”
Section: Introductionunclassified